2015
DOI: 10.1017/s0950268815001466
|View full text |Cite
|
Sign up to set email alerts
|

Calling all Campy – how routine investigation and molecular characterization impacts the understanding of campylobacteriosis epidemiology – Alaska, United States, 2004–2013

Abstract: Unlike most jurisdictions in the United States, Alaska performs pulsed-field gel electrophoresis (PFGE) characterization of all Campylobacter sp. isolates at the state public health laboratory--a practice that started in 2002. Moreover, in order to ensure early detection and response to campylobacteriosis outbreaks, the Alaska Section of Epidemiology has investigated all incident Campylobacter sp. case reports since 2004. This report summarizes the public health impact of routine incident case investigations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…A national surveillance program (FoodNet) in the United States found 0·5% of campylobacteriosis cases reported in 2011 to be outbreak-related [25]. While this suggests >99% of cases are sporadic, recent studies have suggested that this proportion is likely lower and may be closer to 70–75% [26, 27]. Similarly, the findings of this study suggest 73% of cases were sporadic.…”
Section: Discussionsupporting
confidence: 51%
“…A national surveillance program (FoodNet) in the United States found 0·5% of campylobacteriosis cases reported in 2011 to be outbreak-related [25]. While this suggests >99% of cases are sporadic, recent studies have suggested that this proportion is likely lower and may be closer to 70–75% [26, 27]. Similarly, the findings of this study suggest 73% of cases were sporadic.…”
Section: Discussionsupporting
confidence: 51%
“…One such study by Kovanen et al (2016), showed through the use of whole-genome sequencing (WGS) that only one in five campylobacteriosis cases in three Finnish hospital districts was traceable to the Finnish chicken reservoir, and revealed a clustering of human cases without a possible coupling to chicken isolates [ 12 ]. Such diffuse outbreaks, i.e., the occurrence of temporal and/or spatial clusters of genotypically similar isolates among apparently sporadic cases, are suggested to be several times more common than point-source outbreaks for Campylobacter infections [ 13 , 14 , 15 ]. More research is needed to show if such a distribution of cases is a trend or a one-time event.…”
Section: Introductionmentioning
confidence: 99%